Transcatheter arterial embolization for advanced gastric cancer bleeding: A single-center experience with 58 patients. Issue 15 (April 2020) - Cho, Soo Buem; Hur, Saebeom; Kim, Hyo-Cheol; Jae, Hwan Jun; Lee, Myungsu; Kim, Minuk; Kim, Jeong-Eun; Lee, Jae Hwan; Chung, Jin Wook
Abstract : Abstract: To investigate computed tomography and angiography findings and clinical outcomes after transcatheter arterial embolization for acute upper gastrointestinal bleeding from advanced gastric cancers. From January 2005 to December 2014, 58 patients with pathologically proven gastric cancer were treated at our institution with transcatheter arterial embolization due to acute upper gastrointestinal bleeding recalcitrant to endoscopic treatment. The electronic medical records for each patient were reviewed for clinical presentation, endoscopy history, computed tomography and angiographic findings, blood transfusion requirements, and follow-up results. Angiography findings were positive in 13 patients (22.4%): contrast extravasation was found in 9 patients and pseudoaneurysm in 4 patients. All patients with positive angiograms underwent selective embolization treatment. Those with negative angiography findings underwent empirical embolization. Gelfoam, n-butyl cyanoacrylate, coils, or a combination of these were used as embolic agents. The overall clinical success rate was 72.4% (42/58), and the success rate for patients with positive angiography was 53.8% (7/13). The median survival was 97.5 days (range, 7–1415 days), and the 1-month survival rate was 89.6% (52/58). The 1-month survival rate of the clinical success group was 95.2% (40/42), which was significantly higher than that of the clinical failure group ( P  = .04). The clinical success group also required significantly fewer transfusions (2.43 units, range 0–24 units) ( P  = .02). Transcatheter arterial embolization is a highly effective treatment for advanced gastric cancer with active bleeding. It should be considered as an additional treatment, especially when endoscopic or surgical treatment fails or when these approaches are difficult.